2013
DOI: 10.1037/a0032257
|View full text |Cite
|
Sign up to set email alerts
|

The psychological and neurological bases of leader self-complexity and effects on adaptive decision-making.

Abstract: Complex contexts and environments require leaders to be highly adaptive and to adjust their behavioral responses to meet diverse role demands. Such adaptability may be contingent upon leaders having requisite complexity to facilitate effectiveness across a range of roles. However, there exists little empirical understanding of the etiology or basis of leader complexity. To this end, we conceptualized a model of leader self-complexity that is inclusive of both the mind (the complexity of leaders' self-concepts)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
156
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(164 citation statements)
references
References 151 publications
(262 reference statements)
5
156
0
3
Order By: Relevance
“…In the leadership literature, the neuropsychological constructs of cognitive control and decision-making have been linked to transformational leadership, with these leaders showing patterns of resting state electro-encephalographic (EEG) activity reflective of strengths in these two functions (Balthazard et al 2012;Hannah et al 2013). However, the ways in which cognitive control and decision-making come together to influence transformational leadership have not been adequately explored.…”
Section: Executive Function As An Antecedent To Transformational Leadmentioning
confidence: 99%
See 1 more Smart Citation
“…In the leadership literature, the neuropsychological constructs of cognitive control and decision-making have been linked to transformational leadership, with these leaders showing patterns of resting state electro-encephalographic (EEG) activity reflective of strengths in these two functions (Balthazard et al 2012;Hannah et al 2013). However, the ways in which cognitive control and decision-making come together to influence transformational leadership have not been adequately explored.…”
Section: Executive Function As An Antecedent To Transformational Leadmentioning
confidence: 99%
“…The specific executive functions of cognitive Fig. 1 The human prefrontal cortex and its components control (Balthazard et al 2012;Zaccaro et al 1991) and decision-making (Hannah et al 2013;Connelly et al 2000), that have been preliminarily associated with leadership may present relatively thin-sliced mental capacities that can benefit from further exploration. EEG research has indicated that transformational leaders experience low phase lock duration of alpha brain waves in most parts of the brain, perhaps indicating higher cognitive control (especially cognitive flexibility) in these leaders (Balthazard et al 2012).…”
Section: Executive Function As An Antecedent To Transformational Leadmentioning
confidence: 99%
“…Related research suggests that a paradox mindset may have a neurological basis (Hannah, Balthazard, Waldman, Jennings, & Thatcher 2013), and can increase with age and challenging life experiences, as individuals learn to live with tensions and see their long-term benefits (Lomranz & Benyamini, 2016). Intervention studies that have used paradoxical inquiry methods suggest that managers can learn to change their experience of and approaches to tensions (Lüscher & Lewis, 2008).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Within business organizations, leadership is especially relevant for the fair treatment of individuals, and neuroscience methods have recently been used to study the topic. Research to date has focused on individual characteristics of the leader and has investigated the neuroscience basis for complex leadership, i.e., leadership that can meet diverse role demands (Hannah et al, 2013), for inspirational leaders who espouse a high level of regard for others (Waldman et al, 2011) and the relation between empathy, perspective taking, and a Machiavellian leadership style (Bagozzi et al, 2013).…”
Section: Leadershipmentioning
confidence: 99%